CARD INNOVATION IN TEACHING AKIDAH AKHLAK AT MAN 1 MANDAILING NATAL - Dhita Mutiara Permata Sari; Najwa Ahsanah; Husin As'ari Lubis; Syamsiah Depalina Siregar (STKIP Pesisir Selatan, 2026)
This study aims to describe the innovation of using case cards in teaching Akidah Akhlak (Islamic beliefs and morals) at MAN 1 Mandailing Natal. Case cards are designed to present real-life problems related to moral values, thereby encouraging students to think critically and actively participate in the learning process. This study uses a qualitative approach with a classroom action research design. Data collection techniques include observation, student response questionnaires, learning outcome tests, and documentation. The results of the study indicate that the use of case card media can increase student activity, facilitate understanding of religious ethics material, and foster a reflective attitude towards moral issues in everyday life. Thus, case card media can be used as an alternative innovative learning media in religious ethics learning.